1996
DOI: 10.1520/jfs13918j
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Accidental Ingestion of Carbon Tetrachloride: A Postmortem Distribution Study

Abstract: This paper reports a fatality involving a 75-year-old white male, who ingested an unknown quantity of carbon tetrachloride (CCl4)—a toxic agent able to induce central neryous system depression and severe renal and hepatic damage—and who died after two days of intensive care. The analytical assessment of CCl4 concentration was performed on several biological fluids and tissues employing gas chromatography-flame ionization detection (GC-FID) head space method. Both urine (328.5 mg/L) and bile (169.8 mg/L) had hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Medicinal plants extracts and their bioactive metabolites play important role in the prevention of oxidative damages especially CCl 4 induced hepatic and testicular injuries in experimental animals [7, 26]. In the present investigations administration of various fractions of R. hastatus revealed reduction in elevated concentrations of AST, ALT, ALP, and γ GT to maintain the structural consistency of the hepatocellular structure.…”
Section: Discussionsupporting
confidence: 51%
“…Medicinal plants extracts and their bioactive metabolites play important role in the prevention of oxidative damages especially CCl 4 induced hepatic and testicular injuries in experimental animals [7, 26]. In the present investigations administration of various fractions of R. hastatus revealed reduction in elevated concentrations of AST, ALT, ALP, and γ GT to maintain the structural consistency of the hepatocellular structure.…”
Section: Discussionsupporting
confidence: 51%
“…CCl 4 could also have a direct toxic effect (Clemedson et al 1990) through its lipophilic properties, by exposing the sensitive methylene groups of the fatty acid backbone to molecular oxygen. Although the activation of CCl 4 occurs mainly in liver, brain membranes have a high affinity for CCl 4 and the concentration of the chemical seems to be almost independent from the brain zone of sampling (Tombolini and Cingolani 1996). The brain is sensitive to free radical attack (Patole and Ramasarma 1988) because of its elevated consumption of oxygen and the high content of polyunsaturated fatty acids (PUFA) in its cell membranes (Sastry 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plant extracts and their bioactive metabolites have been shown to induce the prevention of oxidative damages which especially from CCl 4 induced hepatic injuries animals studies (26). Antrodia, one of the widely known medicinal mushrooms, belongs to the family Fomitopsidaceae which is valued in Taiwan Our results demonstrated that treatment with CCl 4 promoted a marked increase in serum GPT and GOT activities that were due to liver damage in rats.…”
Section: Discussionmentioning
confidence: 53%